Prognostic and predictive value of primary tumour side in patients with RAS wild-type metastatic colorectal cancer treated with chemotherapy and EGFR directed antibodies in six randomized trials - Arnold, D (2018)
BACKGROUND: There is increasing evidence that metastatic colorectal cancer (mCRC) is a genetically heterogeneous disease and that tumours arising from different sides of the colon (left versus right) have different clinical outcomes. Furthermore, previous analyses comparing the activity of different classes of targeted agents in patients with KRAS wild-type (wt) or RAS wt mCRC suggest that primary tumour location (side), might be both prognostic and predictive for clinical outcome. METHODS: This retrospective analysis investigated the prognostic and predictive influence of the localization of the primary tumour in patients with unresectable RAS wt mCRC included in six randomized trials (CRYSTAL, FIRE-3, CALGB 80405, PRIME, PEAK and 20050181), comparing chemotherapy plus EGFR antibody therapy (experimental arm) with chemotherapy or chemotherapy and bevacizumab (control arms). Hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS) and progression-free survival (PFS) for patients with left-sided versus right-sided tumours, and odds ratios (ORs) for objective response rate (ORR) were estimated by pooling individual study HRs/ORs. The predictive value was evaluated by pooling study interaction between treatment effect and tumour side. RESULTS: Primary tumour location and RAS mutation status were available for 2159 of the 5760 patients (37.5%) randomized across the 6 trials, 515 right-sided and 1644 left-sided. A significantly worse prognosis was observed for patients with right-sided tumours compared with those with left-sided tumours in both the pooled control and experimental arms for OS [HRs = 2.03 (95% CI: 1.69-2.42) and 1.38 (1.17-1.63), respectively], PFS [HRs = 1.59 (1.34-1.88) and 1.25 (1.06-1.47)], and ORR [ORs = 0.38 (0.28-0.50) and 0.56 (0.43-0.73)]. In terms of a predictive effect, a significant benefit for chemotherapy plus EGFR antibody therapy was observed in patients with left-sided tumours [HRs = 0.75 (0.67-0.84) and 0.78 (0.70-0.87) for OS and PFS, respectively] compared with no significant benefit for those with right-sided tumours [HRs = 1.12 (0.87-1.45) and 1.12 (0.87-1.44) for OS and PFS, respectively; P value for interaction <0.001 and 0.002, respectively]. For ORR, there was a trend (P value for interaction = 0.07) towards a greater benefit for chemotherapy plus EGFR antibody therapy in the patients with left-sided tumours [OR = 2.12 (1.77-2.55)] compared with those with right-sided tumours [OR = 1.47 (0.94-2.29)]. Exclusion of the unique phase II trial or the unique second-line trial had no impact on the results. The predictive effect on PFS may depend of the type of EGFR antibody therapy and on the presence or absence of bevacizumab in the control arm. CONCLUSION: This pooled analysis showed a worse prognosis for OS, PFS and ORR for patients with right-sided tumours compared with those with left-sided tumours in patients with RAS wt mCRC and a predictive effect of tumour side, with a greater effect of chemotherapy plus EGFR antibody therapy compared with chemotherapy or chemotherapy and bevacizumab, the effect being greatest in patients with left-sided tumours. These predictive results should be interpreted with caution due to the retrospective nature of the analysis, which was carried out on subpopulations of patients included in these trials, and because none of these studies contemplated a full treatment sequence strategy.